A bio-based benzoxazine monomer, its preparation method and benzoxazine resin

CN122958355APending Publication Date: 2026-10-23GUILIN UNIV OF ELECTRONIC TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611044666.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

本发明的生物基苯并噁嗪单体兼具低熔点加工性和高交联反应活性,依次经预熔融处理和热固化处理制得的苯并噁嗪树脂具有高热稳定性和高阻燃性,克服了现有技术中苯并噁嗪单体加工性能与固化树脂使用性能难以兼顾的问题;此外,本发明的制备过程无需溶剂,反应效率高且易于工业化生产,单体纯化采用乙酸乙酯和/或乙醇等绿色溶剂,实现了合成与纯化全过程的绿色化

Benefits of technology

1、本发明提供了一种生物基苯并噁嗪单体,其分子中同时含有羟乙基和末端炔基,生物基苯并噁嗪单体为或。本发明将羟乙基与炔基同时设计到生物基苯并噁嗪单体分子中,利用羟乙基降低单体熔点、改善加工性能,同时利用炔基在固化过程中与噁嗪环开环反应协同交联,提高交联密度,从而兼顾单体的低熔点加工性和固化树脂的高性能。本发明克服了现有技术中苯并噁嗪单体加工性能与固化树脂使用性能难以兼顾、高刚性多官能度单体熔点过高且溶解性差导致无溶剂合成及成型加工困难、以及引入柔性结构或降低官能度后固化树脂耐热性、热稳定性和阻燃性不足的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122958355A_ABST
    Figure CN122958355A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of thermosetting resin, in particular to a kind of bio-based benzoxazine monomer and its preparation method and benzoxazine resin.The bio-based benzoxazine monomer of the present application simultaneously contains hydroxyethyl and terminal alkyne in molecule, and the bio-based benzoxazine monomer is or The bio-based benzoxazine monomer of the present application has low melting point processability and high crosslinking reaction activity, and the benzoxazine resin after curing has high thermal stability and high flame retardance, which overcomes the problem that the processability of benzoxazine monomer and the use performance of cured resin are difficult to be considered in prior art;In addition, the preparation process of the present application does not need solvent, and the reaction efficiency is high and easy to industrial production, and the monomer purification uses green solvent such as ethyl acetate and / or ethanol, realizes the greenization of whole process of synthesis and purification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of thermosetting resin technology, specifically to a bio-based benzoxazine monomer, its preparation method, and benzoxazine resin. Background Technology

[0002] Benzoxazine resin, as a high-performance thermosetting resin, has shown broad application prospects in high-end fields such as aerospace, electronic packaging, and high-temperature resistant composite matrix due to its comprehensive advantages such as strong molecular structure designability, excellent thermal stability, low curing shrinkage, and outstanding char-forming properties.

[0003] Significant progress has been made in synthesizing benzoxazine resins using biomass as a substitute for fossil fuels. However, balancing the processing properties of benzoxazine monomers with the overall performance of their cured resins remains challenging. Cured resins exhibiting high heat resistance and flame retardancy are typically produced by curing benzoxazine monomers with high rigidity and multifunctionality. However, these monomers often have extremely high melting points and poor solubility, making solvent-free or green solvent synthesis difficult and severely impacting resin molding and processing. For example, benzoxazine Dz-f, prepared from soybean isoflavones and furfurylamine, exhibits excellent thermal stability (Tg = 391℃, 10% thermogravimetric temperature Td10% = 463℃), but its monomer melting temperature is as high as 164℃. Similarly, API-fa, synthesized from apigenin and furfurylamine, has a Tg and initial decomposition temperature of 376℃ and 384℃, respectively, but its monomer melting temperature is as high as 174℃. In summary, an excessive amount of rigid structure in the molecule significantly increases the monomer melting point, severely impairing the resin's processing performance. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this invention provides a bio-based benzoxazine monomer, its preparation method, and a benzoxazine resin. This invention uses bio-based raw material hydroxytyrosol or tyrosol as the phenol source and m-ethynylaniline as the amine source. Through the Mannich condensation reaction of the phenol source, amine source, and paraformaldehyde, a bio-based benzoxazine monomer containing both hydroxyethyl and terminal alkynyl groups is obtained. The bio-based benzoxazine monomer of this invention possesses both low melting point processability and high crosslinking reactivity. The benzoxazine resin obtained by sequentially pre-melting and thermosetting treatments exhibits high thermal stability and high flame retardancy, overcoming the problem in existing technologies where the processability of benzoxazine monomers and the performance of cured resins are difficult to balance. Furthermore, the preparation process of this invention requires no solvent, has high reaction efficiency, and is easy to industrialize. Monomer purification uses green solvents such as ethyl acetate and / or ethanol, achieving a green synthesis and purification process.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first objective of this invention is to provide a bio-based benzoxazine monomer, wherein the bio-based benzoxazine monomer molecule simultaneously contains a hydroxyethyl group and a terminal alkynyl group; the bio-based benzoxazine monomer is... or .

[0006] Preferably, the bio-based benzoxazine monomer is a monofunctional benzoxazine or a bifunctional benzoxazine.

[0007] A second objective of this invention is to provide a method for preparing the above-mentioned bio-based benzoxazine monomer, comprising the following steps: Using tyrosol or hydroxytyrosol as the phenol source, the phenol source, m-ethynyl aniline, and paraformaldehyde were subjected to a Mannich condensation reaction under solvent-free conditions. During the reaction, the formaldehyde generated by the depolymerization of paraformaldehyde first reacted with the primary amine group of m-ethynyl aniline to generate an imine ion intermediate. Subsequently, the imine ion intermediate attacked the carbon atom of the phenolic hydroxyl group, and through electrophilic addition and intramolecular cyclization, a six-membered heterocyclic structure of benzoxazine was constructed to obtain the bio-based benzoxazine monomer.

[0008] Preferably, the molar ratio of tyrosol, meta-ethynyl aniline and paraformaldehyde is 1:0.8~1.2:1.6~3.

[0009] Preferably, the molar ratio of hydroxytyrosol, meta-ethynyl aniline and paraformaldehyde is 1:1.6~2.4:3.2~6.

[0010] Preferably, the conditions for the Mannich condensation reaction are: reaction at 70℃~140℃ for 0.5h~12h.

[0011] The third objective of this invention is to provide a benzoxazine resin, which is prepared by sequentially subjecting the above-mentioned bio-based benzoxazine monomer to a pre-melting treatment and a thermosetting treatment, wherein the benzoxazine resin is a monofunctional benzoxazine resin (poly(T-ac)) or a difunctional benzoxazine resin (poly(HT-ac)).

[0012] Preferably, the pre-melting treatment conditions are: in a vacuum environment, at 70℃~150℃ for 5min~30min.

[0013] Preferably, the heat curing conditions are: heat treatment at 180℃~240℃ for 2h~6h.

[0014] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention provides a bio-based benzoxazine monomer, the molecule of which simultaneously contains a hydroxyethyl group and a terminal alkyne group. The bio-based benzoxazine monomer is... or This invention incorporates both hydroxyethyl and alkynyl groups into the bio-based benzoxazine monomer molecule. The hydroxyethyl group lowers the monomer's melting point and improves its processing performance, while the alkynyl group synergistically crosslinks with the oxazine ring during curing, increasing the crosslinking density. This achieves a balance between the low melting point of the monomer and the high performance of the cured resin. This invention overcomes the problems in existing technologies, such as the difficulty in balancing the processing performance of benzoxazine monomers with the performance of cured resins, the high melting point and poor solubility of high-rigidity, multifunctional monomers leading to difficulties in solvent-free synthesis and molding, and the insufficient heat resistance, thermal stability, and flame retardancy of cured resins after introducing flexible structures or reducing functionality.

[0015] 2. This invention also provides a method for preparing a bio-based benzoxazine monomer. Using tyrosol or hydroxytyrosol as the phenol source, the method involves a Mannich condensation reaction of the phenol source, m-ethynylaniline, and paraformaldehyde under solvent-free conditions. During the reaction, the formaldehyde generated from the depolymerization of paraformaldehyde first reacts with the primary amine group of m-ethynylaniline to generate an imine ion intermediate. Subsequently, this intermediate attacks the adjacent carbon atom of the phenolic hydroxyl group, undergoing electrophilic addition and intramolecular cyclization to finally construct a six-membered heterocyclic structure of benzoxazine. The preparation process of this invention requires no solvent, has higher reaction efficiency, and is easier to implement for industrial production. Monomer purification uses green solvents such as ethyl acetate and / or ethanol, thus achieving a green synthesis and purification process.

[0016] 3. The present invention also provides a benzoxazine resin, which is prepared by thermosetting the bio-based benzoxazine monomer obtained in the present invention. In the cured resin, the oxazine ring undergoes a ring-opening polymerization reaction, and the terminal alkyne group undergoes a cross-linking reaction to form a network structure with high cross-linking density, thereby endowing the resin with excellent thermal stability and flame retardant properties. Attached Figure Description

[0017] Figure 1 For example, the T-ac of Example 1 and the HT-ac of Example 4 1 HNMR images, where (a) is T-ac and (b) is HT-ac.

[0018] Figure 2 T-ac of Example 1 and T-ac of Example 4 13 CNMR images, where (a) is T-ac and (b) is HT-ac.

[0019] Figure 3 The images show the FTIR spectrum and high-resolution mass spectrum of T-ac in Example 1 and Example 4, where (a) is the FTIR spectrum, (b) is the high-resolution mass spectrum of T-ac, and (c) is the high-resolution mass spectrum of HT-ac.

[0020] Figure 4The images are DSC diagrams of T-ac in Example 1 and DSC diagrams of HT-ac in Example 4, where (a) is T-ac and (b) is HT-ac. The illustration in (a) is a physical image of T-ac at 110°C and the illustration in (b) is a physical image of HT-ac at 110°C.

[0021] Figure 5 T-ac of Example 1 and T-ac of Example 4 -1 / Fitted curve and -1 / The fitted curve is shown in the figure, where (a) is -1 / (b) is -1 / .

[0022] Figure 6 The images are FTIR plots of T-ac and poly(T-ac) of Example 1 and HT-ac and poly(HT-ac) of Example 4, where (a) is T-ac and poly(T-ac) of Example 1 and (b) is HT-ac and poly(HT-ac) of Example 4.

[0023] Figure 7 The curing mechanism diagrams are for T-ac in Example 1 and HT-ac in Example 4.

[0024] Figure 8 The Tg and TGA plots are for poly(T-ac) in Example 1 and poly(HT-ac) in Example 4, where (a) is the Tg plot and (b) is the TGA plot.

[0025] Figure 9 The graphs show the heat release rate (HRR) and total heat release (THR) of poly(T-ac) in Example 1 and poly(HT-ac) in Example 4, where (a) is the heat release rate graph and (b) is the total heat release graph.

[0026] Figure 10 This is a comparison chart of the Tg and HRC values ​​of poly(HT-ac) in Example 4.

[0027] Figure 11 The images show the three-dimensional infrared spectra of the volatile products and the infrared spectra of the pyrolysis gas of poly(T-ac) in Example 1 and poly(HT-ac) in Example 4, where (a) and (b) are the three-dimensional infrared spectra of the volatile products, (c) and (d) are the infrared spectra of the pyrolysis gas, and (a) and (c) are poly(T-ac), and (b) and (d) are poly(HT-ac). Detailed Implementation

[0028] The technical solution of the present invention will be clearly and completely described below with reference to the data in the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0029] It should be noted that the technical terms used in this invention are for the purpose of describing specific embodiments only and are not intended to limit the scope of protection of this invention. Unless otherwise specified, all raw materials, reagents, instruments, and equipment used in the following embodiments of this invention can be purchased commercially or prepared by existing methods. Tyrosol, paraformaldehyde, and m-ethynylaniline were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., China. Hydroxytyrosol was purchased from Nanjing Hegu Life Biotechnology Co., Ltd. All raw materials were analytical grade.

[0030] In existing technologies, the contradiction between the processing performance of benzoxazine monomers and the performance of cured resins remains unresolved. Introducing flexible structures into monomers is an effective strategy to lower the melting point, but flexible segments are prone to decomposition at high temperatures, severely impairing the heat resistance, thermal stability, and flame retardancy of the cured resin. Another strategy to lower the monomer melting point is to reduce the functionality of benzoxazine: typically, monofunctional benzoxazines have significantly lower melting points than difunctional and trifunctional monomers with the same structure, but monofunctional monomers have lower crosslinking densities, leading to insufficient heat resistance in the cured resin.

[0031] To address the problems existing in the prior art, this invention provides a bio-based benzoxazine monomer, wherein the bio-based benzoxazine monomer molecule simultaneously contains a hydroxyethyl group and a terminal alkynyl group; the bio-based benzoxazine monomer is... or This invention incorporates both hydroxyethyl and alkynyl groups into the bio-based benzoxazine monomer molecule. The hydroxyethyl group lowers the monomer's melting point and improves processability, while the alkynyl group synergistically crosslinks with the oxazine ring-opening reaction during curing, increasing the crosslinking density. This balances the low melting point of the monomer with the high performance of the cured resin. Specifically, hydroxyethyl is one of the few groups that can significantly lower the monomer's melting point without significantly sacrificing the performance of the cured resin. This is because its flexible chain segment is sufficiently short, and the hydroxyl group can be firmly anchored in the cured network through hydrogen bonding. Furthermore, the crosslinking reaction of the alkynyl group has good temperature compatibility with the benzoxazine ring-opening reaction, occurring within a similar curing temperature range, significantly increasing the crosslinking density of the cured benzoxazine resin.

[0032] To enable those skilled in the art to more clearly understand the technical solution of the present invention, the following will provide a detailed description in conjunction with specific embodiments: Example 1 A method for preparing a bio-based benzoxazine monomer, the technical route of which is as follows: The steps include: Using tyrosol as the phenol source and m-ethynylaniline as the amine source, tyrosol (5.897 g, 0.043 mol), m-ethynylaniline (5 g, 0.043 mol), and paraformaldehyde (2.564 g, 0.085 mol) were added to a three-necked flask, stirred in an oil bath, and subjected to a Mannich condensation reaction at 100 °C for 1 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The crude product was dissolved in ethyl acetate, and the insoluble matter was removed by filtration. The filtrate was added dropwise to ethanol to precipitate crystals. After filtration, the crystals were washed with ethanol, filtered under vacuum, and dried in a vacuum oven at 50 °C for 12 h to obtain a yellow powder product, namely a benzoxazine monomer containing ethynyl and hydroxyethyl groups, denoted as T-ac, 10.781 g, with a yield of 90.17%.

[0033] Hydrogen NMR spectrum (500 MHz, deuterated chloroform): 7.25 (quartet, 2H, J=15 Hz, aromatic ring hydrogen), 7.11 (doublet, 2H, J=20 Hz, aromatic ring hydrogen), 7.00 (doublet, 1H, J=5 Hz, aromatic ring hydrogen), 6.89 (singlet, 1H, aromatic ring hydrogen), 6.80 (doublet, 1H, aromatic ring hydrogen), 5.35 (singlet, 2H, -O-CH2-N-), 4.63 (singlet, 2H, -Ar-CH2-O-), 3.82 (singlet, 2H, -CH2-), 3.08 (singlet, 1H, alkyne hydrogen), 2.78 (singlet, 2H, -CH2-).

[0034] Carbon NMR spectra (500 MHz, deuterated chloroform): δ 125.81, 148.29, 131.06, 129.35, 128.56, 127.23, 125.09, 122.96, 121.45, 120.60, 118.73, 117.10, 83.86, 78.83, 63.63, 50.42, 38.37.

[0035] A method for preparing a benzoxazine resin, the curing mechanism diagram is shown below. Figure 7 As shown in (a), the steps include: The bio-based benzoxazine monomer was placed on an iron plate covered with a release cloth and transferred to a vacuum drying oven. Under vacuum conditions, the temperature was raised to 120°C and held for 30 minutes for pre-melting. At the same time, the forced-air drying oven was started in advance and the program was set as follows: 180°C for 1 hour, 200°C for 1 hour, 220°C for 1 hour, and 240°C for 2 hours. After the vacuum treatment was completed, the gas was released, and the molten monomer was quickly transferred to the forced-air drying oven and cured according to the above program to obtain benzoxazine resin, denoted as poly(T-ac).

[0036] Example 2 A method for preparing a bio-based benzoxazine monomer is the same as the method in Example 1, except that the amount of meta-ethynylaniline is replaced from 0.043 mol to 0.0344 mol, and the amount of paraformaldehyde is replaced from 0.085 mol to 0.0688 mol, to obtain the bio-based benzoxazine monomer.

[0037] Example 3 A method for preparing a bio-based benzoxazine monomer is the same as the method in Example 1, except that the amount of meta-ethynylaniline is replaced from 0.043 mol to 0.0516 mol and the amount of paraformaldehyde is replaced from 0.085 mol to 0.129 mol, thereby obtaining the bio-based benzoxazine monomer.

[0038] Example 4 A method for preparing a bio-based benzoxazine monomer, the technical route of which is as follows: The steps include: Using hydroxytyrosol as the phenol source and m-ethynylaniline as the amine source, hydroxytyrosol (3.291 g, 0.021 mol), m-ethynylaniline (5 g, 0.043 mol), and paraformaldehyde (2.564 g, 0.085 mol) were added to a three-necked flask, stirred in an oil bath, and subjected to a Mannich condensation reaction at 100 °C for 1 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature. The crude product was dissolved in ethyl acetate, and the insoluble matter was removed by filtration. The filtrate was added dropwise to ethanol to precipitate crystals. After filtration, the crystals were washed with ethanol, filtered under vacuum, and dried in a vacuum oven at 50 °C for 12 h to obtain a black powder, namely a benzoxazine monomer containing ethynyl and hydroxyethyl groups, denoted as HT-ac, with a mass of 7.607 g and a yield of 81.53%.

[0039] Hydrogen NMR spectrum (500 MHz, deuterated chloroform): 7.18 (multiplex, 8H, aromatic ring hydrogen), 6.47 (single, 1H, aromatic ring hydrogen), 5.42 (doublet, 4H, -O-CH2-N-), 4.61 (doublet, 4H, -Ar-CH2-O-), 3.84 (triplet, 2H, -CH2-), 3.07 (singlet, 2H, alkyne hydrogen), 2.73 (singlet, 2H, -CH2-).

[0040] Carbon NMR spectra (500 MHz, deuterated chloroform): δ 148.13, 143.06, 141.52, 129.34, 127.38, 125.18, 122.94, 121.49, 119.59, 118.76, 83.77, 79.15, 78.78, 62.75, 50.11, 48.47, 34.35.

[0041] A method for preparing a benzoxazine resin, the curing mechanism diagram is shown below. Figure 7 As shown in (b), the steps include: The bio-based benzoxazine monomer was placed on an iron plate covered with a release cloth and transferred to a vacuum drying oven. Under vacuum conditions, the temperature was raised to 120°C and held for 30 minutes for pre-melting. At the same time, the forced-air drying oven was started in advance and the program was set as follows: 180°C for 1 hour, 200°C for 1 hour, 220°C for 1 hour, and 240°C for 2 hours. After the vacuum treatment was completed, the gas was released, and the molten monomer was quickly transferred to the forced-air drying oven and cured according to the above program to obtain benzoxazine resin, denoted as poly(HT-ac).

[0042] Example 5 A method for preparing a bio-based benzoxazine monomer is the same as that in Example 4, except that the amount of meta-ethynylaniline is replaced from 0.043 mol to 0.0336 mol and the amount of paraformaldehyde is replaced from 0.085 mol to 0.0672 mol, thus obtaining the bio-based benzoxazine monomer.

[0043] Example 6 A method for preparing a bio-based benzoxazine monomer is the same as the method in Example 4, except that the amount of meta-ethynylaniline is replaced from 0.043 mol to 0.054 mol, and the amount of paraformaldehyde is replaced from 0.085 mol to 0.126 mol, to obtain the bio-based benzoxazine monomer.

[0044] Performance testing: like Figure 1(a) is the T-ac 1H spectrum, as shown in the figure. The range of 6.7ppm to 7.2ppm is the characteristic peak of the aromatic hydrogen of the benzene ring; the proton peaks of -O-CH2-N and Ar-CH2-N on the oxazine ring appear at 5.4ppm (H1) and 4.6ppm (H2), respectively; 3.8ppm (H3) and 2.8ppm (H5) are attributed to the hydroxyethyl proton; 3.1ppm (H4) is the ethynyl hydrogen absorption peak. Figure 1 (b) shows the HT-ac proton spectrum, which also shows all the characteristic hydrogen signals: benzene ring hydrogen (6.7ppm~7.2ppm), oxazine ring hydrogen (5.4ppm, 4.6ppm), hydroxyethyl hydrogen (3.8ppm, 2.7ppm), and ethynyl hydrogen (3.1ppm). The proton spectrum has no impurity peaks, proving that the two bio-based benzoxazine monomers were successfully synthesized with high purity.

[0045] like Figure 2 As shown, the characteristic carbon signals of the oxazine ring O-CH2-N and Ar-CH2-N in T-ac are located at 78.83 ppm and 50.42 ppm, respectively; the characteristic carbon signals of hydroxyethyl and ethynyl groups are located at 38.37 ppm, 63.63 ppm, and 83.86 ppm, respectively; the corresponding characteristic carbon signals of HT-ac are 78.78 ppm, 50.11 ppm, 34.35 ppm, 62.75 ppm, and 83.77 ppm, further confirming that the monomer molecular structure is consistent with the design.

[0046] The FTIR spectra of the two bio-based benzoxazine monomers, T-ac and HT-ac, are shown below. Figure 3 As shown in (a), both exhibit the characteristic absorption peaks of benzoxazine: COC symmetric stretching vibration (1043 cm⁻¹). -1 1046cm -1 Asymmetric stretching vibration (1235cm) -1 1236cm -1 ), oxazine ring characteristic peak (903 cm⁻¹) -1 944cm -1 ); 3205, 3280cm -1 The strong absorption peak is attributed to the ≡CH stretching vibration, 2104 cm⁻¹ -1 2106cm -1 The weak absorption peak corresponds to the stretching vibration of the -C≡C- triple bond, and the above characteristic peaks prove that the two monomers were successfully prepared.

[0047] like Figure 3 As shown in (b) and (c), the measured molecular ion peak m / z of T-ac and HT-ac are 280.1343 and 437.1883, respectively; corresponding to the molecular formula [C 18 H 17 NO2+H] + [C]28 H 24 N2O3+H] + The theoretical precise masses are 279.1337 and 437.1865, respectively. The mass deviation is far below the industry-standard allowable error range of 5 ppm. The measured values ​​are in high agreement with the theoretical mass-to-charge ratio, further confirming that the two substances are T-ac and HT-ac.

[0048] Figure 4 The non-isothermal differential scanning calorimetry (DSC) curves for T-ac and HT-ac are shown, with a test temperature range of 50℃ to 300℃. The vertical axis represents heat flow rate, and Exo upwards represents exothermic effects. The 10℃ / min heating curve shows both an endothermic melting peak and a symmetrical exothermic curing peak, corresponding to monomer melting and curing crosslinking behaviors, respectively. The melting temperature T of T-ac is shown. m =85.2℃; HT-ac has no obvious melting peak because of its low molecular symmetry and poor crystallinity, resulting in no clear melting transition. However, the actual photos show that HT-ac is completely liquid at 110℃, and its viscosity is higher than that of T-ac at the same temperature, still proving that it has low melting point characteristics. The peak curing temperature T of T-ac and HT-ac is... p The temperatures were 241.1℃ and 221.9℃ respectively, indicating that the oxazine ring-opening polymerization and the acetylene crosslinking reaction occurred within a similar temperature range. The large difference between the melting temperature and the peak curing temperature of the two monomers indicates a wide processing window and excellent molding and processing performance.

[0049] To investigate the curing reaction characteristics of monofunctional and difunctional benzoxazine resins, differential scanning calorimetry (DSC) was used to conduct non-isothermal curing tests on the two benzoxazine resins at different heating rates (2℃ / min, 5℃ / min, 10℃ / min, 15℃ / min, 20℃ / min). The activation energy of the benzoxazine resin polymer reaction was calculated using the Kissinger method (Equation 1) and the modified Ozawa method (Equation 2).

[0050] (Equation 1).

[0051] (Equation 2).

[0052] In the Kissinger formula, For the heating rate, This is the peak temperature of the curing curve. Here, A is the activation energy of the reaction, A is the frequency factor, and R is the universal gas constant; within the Ozawa formula... , R has the same meaning, C is the relevant constant and C = .

[0053] Based on the heating rate β and its corresponding curing exothermic peak temperature T p Kissinger method was used respectively. -1 / ) and Ozawa method (ln(β)−1 / T p Perform linear fitting, such as Figure 5 As shown in the figure. The calculation results show that the apparent activation energies of T-ac are 86.6 kJ / mol (Kissinger method) and 90.3 kJ / mol (Ozawa method), respectively; while the apparent activation energies of HT-ac are 91.7 kJ / mol (Kissinger method) and 94.9 kJ / mol (Ozawa method), respectively. The curing activation energies of both monomers are at relatively low levels, indicating their high reactivity, which is beneficial for achieving low-temperature curing. Among them, the activation energy of the bifunctional HT-ac is slightly higher than that of the monofunctional T-ac due to its greater steric hindrance. It should be noted that, due to the complexity of the polymerization reaction systems of T-ac and HT-ac, the above calculation results are all apparent activation energies.

[0054] like Figure 6 As shown, in the FTIR spectrum of the cured resin, the absorption peaks corresponding to the symmetric and asymmetric stretching vibrations of the oxazine ring COC (1034 cm⁻¹) are... -1 / 1036cm -1 1235cm -1 / 1236cm -1 ) and the vibrational peak of the oxazine ring skeleton (903 cm⁻¹) -1 / 944cm -1 The intensity of the radiation significantly decreased or even disappeared at 3400cm. -1 The presence of a characteristic absorption peak for hydroxyl groups nearby indicates that both bio-based benzoxazine monomers underwent oxazine ring-opening polymerization. Furthermore, the characteristic peak attributable to the acetylene group in the T-ac and HT-ac molecules (≡CH stretching vibration: 3205 cm⁻¹) is also present. -1 / 2104cm -1 -C≡C- stretching vibration: 3280cm -1 / 2106cm -1 The acetylene group also significantly weakened or disappeared, indicating that the acetylene group participated in the curing and crosslinking reaction and was transformed into an olefin or aromatic ring structure and incorporated into the resin network.

[0055] The curing mechanisms of the two benzoxazine resins are as follows: Figure 7 As shown: the oxazine ring undergoes ring-opening polymerization to form a phenolic hydroxyl crosslinking network, while the acetylene group undergoes a thermal crosslinking reaction to form additional crosslinking points; the additional crosslinking effect of the acetylene group and the hydrogen bond network constructed by the hydroxyethyl group produce a synergistic effect, which together endows the benzoxazine resin with excellent thermal stability and flame retardant properties.

[0056] The thermal properties of thermosetting resins mainly include thermal stability and heat resistance, typically evaluated using the initial thermal decomposition temperature (Tdi) and glass transition temperature (Tg) as typical indicators. These two factors together determine the resin's maximum service temperature. Tg is determined by the peak value of the loss factor tanδ in dynamic mechanical analysis (DMA). Figure 8 As shown in (a), the glass transition temperatures (Tg) of poly(T-ac) and poly(HT-ac) reach 332℃ and 386℃, respectively, significantly higher than those of commercially available benzoxazine resins. Taking the most mature commercially available bisphenol A type benzoxazine (BA-a) as a reference, although it possesses excellent processing properties (Tm=111℃) and balanced overall performance, its Tg is only 168℃. The ultra-high glass transition temperatures of the two benzoxazine resins of this invention are mainly due to the following two aspects: firstly, the acetylene-based thermal polymerization reaction significantly increases the crosslinking density of the benzoxazine resin; secondly, the hydroxyethyl group promotes the formation of a high-density hydrogen bond network within the benzoxazine resin. These superior properties fully demonstrate the rationality and feasibility of the molecular design concept of this invention. Furthermore, since the crosslinking density of poly(HT-ac) obtained by curing the bifunctional monomer is higher than that of the monofunctional poly(T-ac), its Tg is also correspondingly higher.

[0057] Thermogravimetric analysis (TGA) was used to evaluate the thermal stability of the two benzoxazine resins, and the results are as follows: Figure 8 As shown in (b), the initial thermal decomposition temperatures (Tdi) of poly(T-ac) and poly(HT-ac) are 387℃ and 388℃, respectively, demonstrating outstanding thermal stability. Their char residue rates (Yc) at 800℃ are 56.3% and 70.1%, respectively, with poly(HT-ac) exhibiting superior char-forming ability. The partial conversion of the acetylene group to a benzene ring structure during crosslinking is the core reason for the high char residue rate of the benzoxazine resins; this high char-forming characteristic gives both polybenzoxazine resins the potential to be used as flame-retardant materials.

[0058] Flame retardancy is one of the key indicators of high-performance materials. The flame retardant properties of poly(T-ac) and poly(HT-ac) were characterized using a micro combustion calorimeter (MCC). Their heat release rate (HRR) and total heat release (THR) curves are shown below. Figure 9As shown in the figure, the peak value of the HRR curve, i.e., the heat release capacity (HRC), is a core parameter for evaluating the combustion behavior of materials and predicting their flammability. According to industry-standard criteria: HRC < 300 J / (g·K) indicates a self-extinguishing polymer, and HRC < 100 J / (g·K) indicates a non-combustible polymer. Test results show that the HRC values ​​of poly(T-ac) and poly(HT-ac) are 134.3 J / (g·K) and 57.1 J / (g·K), respectively, proving that poly(T-ac) is a self-extinguishing material, and that the HRC value of poly(HT-ac) meets the criteria for a non-combustible polymer (HRC < 100 J / (g·K)). Their THR values ​​are 12.1 kJ / g and 7.1 kJ / g, respectively, demonstrating excellent performance in both core flame-retardant indicators. In comparison, the HRC of commercially available BA-a benzoxazine is 328 J / (g·K) and the THR is 35.3 kJ / g, both significantly higher than the two benzoxazine resins of this invention. It is noteworthy that both poly(T-ac) and poly(HT-ac) are free of halogens and phosphorus, which is of great significance for environmental protection and human health.

[0059] Limiting oxygen index (LOI) is a key parameter for evaluating the flame retardant properties of polymers and is closely related to high-temperature char residue. It is calculated using the van Krevelen equation (Equation 3): LOI(%) = 0.4Yc + 17.5 (Equation 3).

[0060] Polymers with an LOI > 26% are classified as self-extinguishing materials. Calculations show that the LOIs of poly(T-ac) and poly(HT-ac) are 40.0% and 45.4%, respectively, which are far higher than the self-extinguishing critical value. The key performance of poly(T-ac) and poly(HT-ac) is summarized in Table 1.

[0061] Table 1 shows the key performance indicators of poly(T-ac) and poly(HT-ac). Glass transition temperature (Tg) and heat release capacity (HRC) were selected as core evaluation indicators to conduct a comparative analysis of poly(T-ac), poly(HT-ac), and bio-based flame-retardant benzoxazine resins reported in existing literature. Figure 10As shown, in the Tg-HRC coordinate system, the ideal resin should have both high Tg (high heat resistance) and low HRC (high flame retardancy), which is located in the upper left corner of the figure. Among the low-melting-point benzoxazine system (blue dots) with monomer melting points not higher than 110℃, poly(HT-ac) (red pentagram above) has both the highest Tg (386℃) and the lowest HRC (57.1W / g), which is significantly better than other low-melting-point resins, achieving an excellent balance between processing performance and flame retardant and heat resistance. Furthermore, even compared with all the reported bio-based flame retardant benzoxazine resins (including high-melting-point systems marked with hollow triangles), the Tg of poly(HT-ac) is only lower than that of two magnolnitrile benzoxazines, poly(M-mBN) and poly(M-pBN) (△

[44] ), but the monomer melting points of the latter two are as high as 164℃ and 187℃, respectively, and their molding and processing performance is far inferior to that of the material of this invention. This result fully demonstrates that the present invention has successfully broken through the technical bottleneck of the difficulty in balancing low melting point processability and high heat resistance and flame retardancy through molecular design, and has achieved Pareto optimality in comprehensive performance among low melting point benzoxazine resins.

[0062] Among them,

[20] W. Zhang, J. Meng, Y. Zou, C. Ma, Y. Liu, Development ofHydroxytyrosol-Derived Benzoxazine Resins with Excellent Heat-Resistance andFlame Retardancy by a Solvent-Free Method, ACS Appl. Polym. Mater. 7(14)(2025) 9338-9348.

[0063]

[21] W. Zhang, G. Li, C. Yi, H. Zhou, B. Huang, J. Meng, Y. Zou, C.Ma, Y. Liu, Developing biobased benzoxazine resins with excellent processability, thermal stability, flame retardancy and dielectricproperties, Eur. Polym. J. 242 (2026) 114436.

[0064]

[33] Y. Lu, Y. Zhang, K. Zhang, Renewable biomass resources to access halogen- and phosphorus-free flame retardant thermosets with ultra-low heat release capacity, Chem. Eng. J. 448 (2022) 137670.

[0065]

[35] Y. Liu, L. Yuan, G. Liang, A. Gu, Preparation of Thermally Resistant and Mechanically Strong Biomass Benzoxazine Resins via Green Strategy, ACS Sustainable Chem. Eng. 12(3) (2024) 1247-1254.

[0066]

[37] R. Yuan, Y. Lu, W. Sheng, K. Zhang, Synthesis and Characterization of Asymmetric Bio-Based Bisbenzoxazine with a Single Diethyl Phosphite Substituted Oxazine Ring, ACS Appl. Polym. Mater 8(3) (2026) 1996-2006.

[0067]

[38] M. Wu, C. Chen, A. Peng, Z. Zeng, Z. Zhang, X. Liu, Y. Huang, Self-catalyzed bio-benzoxazines containing phthalonitrile with high thermal stability and intrinsic flame retardancy as well as its composite reinforced by aramid fiber, Polym. Degrad. Stab. 242 (2025) 111705.

[0068]

[40] X. Zhang, M. Li, Z. Zhu, Y. Jiang, Green Strategy for Preparing Multifunctional Biobased Benzoxazine Resins Derived from Renewable Phenolic Acids, ACS Appl. Polym. Mater. 8 (2026) 5c04392.

[0069]

[41] X.-Z. Yang, Z. Yan, Z. Yang, B. Qian, Z. Liu, R. Lv, Z. Fei, X.-L. Sha, Acetal-derived biomass benzoxazine resins: Excellent heat resistance, mechanical properties and flame retardant properties, Chem. Eng. J. 513 (2025) 162617.

[0070]

[44] X. Zhang, P. Li, F. Zuo, X. Wang, X.-L. Sha, Renewable Magnolol-Derived Benzoxazine Resins with Ultrahigh Glass Transition Temperature, Superior Flame Retardancy, and Valorization into High-Performance CO₂ Adsorption, ACS Appl. Polym. Mater. 7(23) (2025) 16206-16216.

[0071]

[45] is Z.-Q. Qin, X. Wang, H.-R. Qin, X.-Y. Lan, B.-X. Ou, Y. Hu, L. Song, A Bio-Based Polybenzoxazine Derived from Diphenolic Acid with Intrinsic Flame Retardancy, High Glass Transition Temperature and Dielectric Properties, Macromol. Rapid Commun. 46(2) (2025) 2400666.

[0072]

[46] is L. Chen, Y. Hu, J. Wang, Furan-derived biobased polybenzoxazines with intrinsic flame retardancy and high thermal stability, New J. Chem. 49(39) (2025) 17149-17158.

[0073]

[47] is Z. Wang, Q. Chen, T. Liu, X. Wang, A.A. Khan Gorar, W.-b. Liu, J. Wang, J.-y. Wang, Synthesis of bio-based tetrafunctional benzoxazines derived from furfurylamine: Excellent heat resistance and flame retardant properties, Polymer 326 (2025) 128306.

[0074]

[48] is H. Yan, C. Sun, Z. Fang, X. Liu, J. Zhu, H. Wang, Synthesis of an intrinsically flame retardant bio-based benzoxazine resin, Polymer 97 (2016) 418-427.

[0075]

[51] Z. Feng, R. Xiang, J. Huang, M. Zeng, A novel bio-basedpolybenzoxazine prepared from fluorinated Schiff base and furfurylamine with superior thermal, flame-retardant and superhigh-frequency low dielectric properties, React. Funct. Polym. 221 (2026) 106654.

[0076] Figure 11 (a) and (b) are three-dimensional infrared spectra of the volatile products of thermal degradation of two benzoxazine resins, which intuitively reflect the trend of changes in the types and relative concentrations of degradation products during the heating process. The types of degradation products are basically the same, but the poly(T-ac) absorption peak intensity is higher and the thermal decomposition product release is greater, which is consistent with the TGA test results of residual carbon. Figure 11 (c) and (d) are infrared spectra of pyrolysis gases at typical degradation temperatures. The characteristic absorption peaks of the high-temperature volatilization products correspond to phenols (3400 cm⁻¹). -1 ~4000cm -1 ), CO2 (2354cm) -1 2314cm -1 ), aromatic compounds (1300cm) -1 ~1600cm -1 ), NH3 (964cm) -1 930cm -1 Hydrocarbons (3020cm) -1 Phenolic substances can capture combustion free radicals and interrupt the combustion chain reaction; non-combustible gases such as CO2 and NH3 dilute the oxygen concentration in the flame zone, and the gas phase dilution effect together endows the two benzoxazine resins with excellent flame retardant properties.

[0077] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range, as well as any value between the two endpoints, can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described here to avoid redundancy. Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this invention.

Claims

1. A bio-based benzoxazine monomer, characterized in that, The bio-based benzoxazine monomer molecule contains both hydroxyethyl and terminal alkynyl groups; The bio-based benzoxazine monomer is or .

2. A method for preparing the bio-based benzoxazine monomer according to claim 1, characterized in that, Includes the following steps: Using tyrosol or hydroxytyrosol as the phenol source, the phenol source, meta-ethynyl aniline and paraformaldehyde were subjected to a Mannich condensation reaction under solvent-free conditions to obtain a bio-based benzoxazine monomer.

3. The preparation method according to claim 2, characterized in that, When tyrosol is used as the phenol source, the bio-based benzoxazine monomer is When hydroxytyrosol is used as the phenol source, the bio-based benzoxazine monomer is... .

4. The preparation method according to claim 3, characterized in that, in, The molar ratio of tyrosol, meta-ethynyl aniline and paraformaldehyde is 1:0.8~1.2:1.6~3.

5. The preparation method according to claim 3, characterized in that, The molar ratio of hydroxytyrosol, meta-ethynyl aniline and paraformaldehyde is 1:1.6~2.4:3.2~6.

6. The preparation method according to claim 2, characterized in that, The conditions for the Mannich condensation reaction are: reaction at 70℃~140℃ for 0.5h~12h.

7. A benzoxazine resin, characterized in that, The benzoxazine resin is prepared by sequentially pre-melting and thermosetting of the bio-based benzoxazine monomer as described in claim 1, wherein the benzoxazine resin is a monofunctional benzoxazine resin or a difunctional benzoxazine resin.

8. The benzoxazine resin according to claim 7, characterized in that, When the bio-based benzoxazine monomer is When the benzoxazine resin is a monofunctional benzoxazine resin; When the bio-based benzoxazine monomer is When the benzoxazine resin is used, it is a bifunctional benzoxazine resin.

9. The benzoxazine resin according to claim 7, characterized in that, The pre-melting treatment conditions are: in a vacuum environment, heat at 70℃~150℃ for 5min~30min.

10. The benzoxazine resin according to claim 7, characterized in that, The conditions for thermosetting are: heat treatment at 180℃~240℃ for 2h~6h.